2018
DOI: 10.1038/s41598-018-35295-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Comparison of the Performance of Cutting Bone and Soft Tissue between Piezosurgery and Conventional Rotary Instruments

Abstract: Piezosurgery is an innovative technique widely used for osteotomies in the field of oral and maxillofacial surgery. The surgical technique has been clinically supposed to cut mineralized bone selectively with reducing the risk of damage to adjacent soft tissues. However, none of the previous literature has reported any evidence of scientific experiments to examine performance of the piezoelectric device, i.e. the time required for cutting bone and the effect on soft tissues under the standardized conditions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…In the present study, whose major strength lies in the high number of treated cases, the non-aggressiveness and safety of the piezoelectric bone scalpel were also confirmed by the histology, which showed the absence of necrosis along with vitality of the osteocytes and osteoblasts. Similar results have been reported in the literature [62][63][64][65][66][67]. Piezosurgery has also been reported to interfere to a lesser extent than drills with the initial phases of the bone healing, mainly because it stimulates the bone morphogenetic proteins.…”
Section: Discussionsupporting
confidence: 87%
“…In the present study, whose major strength lies in the high number of treated cases, the non-aggressiveness and safety of the piezoelectric bone scalpel were also confirmed by the histology, which showed the absence of necrosis along with vitality of the osteocytes and osteoblasts. Similar results have been reported in the literature [62][63][64][65][66][67]. Piezosurgery has also been reported to interfere to a lesser extent than drills with the initial phases of the bone healing, mainly because it stimulates the bone morphogenetic proteins.…”
Section: Discussionsupporting
confidence: 87%
“…Piezoelectric tooling for implant site preparation is gaining in popularity. In general, the advantages of piezotools over conventional cylindrical burs involve greater control of the device and selective cutting of mineralized bone (Otake et al, ). A recent meta‐analysis also indicated that implant stability was greater for piezosurgeries when compared with cylindrical bur site preparation with marginal bone levels comparable for both groups (Atieh, Alsabeeha, Tawse‐Smith, & Duncan, ).With the bone and implant performing either the same or better during piezosurgeries, it continues to be a promising solution for osteotomies, where piezosurgery does not perform as well is in surgery time and tool robustness.…”
Section: Discussionmentioning
confidence: 99%
“…It is currently used in bone surgery for small and precise cuts and in areas where sparing soft tissues is critical. Piezoelectric cutting tools operating at frequencies between 25 and 30 kHz are unable to cut soft tissue but are able to make precise cuts into mineralized bone (Otake, Nakamura, Henmi, Takahashi, & Sasano, ). This has been shown clinically to reduce obscuring of the cut by blood and is projected to improve future osseointegration of implants (Landes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It included six randomized clinical trials from 2015. to 2019. and additionaly proved that PEI has no longer duration in surgery, unlike some previous trials have suggested [13]. The study by Otake et al was the first to prove the clinical advantage of PEI in the soft tissue [14]. In most studies reporting the superiority of piezosurgery, the evaluations are mostly based on clinical observations.…”
Section: Casementioning
confidence: 99%